EGFR is required for FOS‐dependent bone tumor development via RSK2/CREB signaling. Issue 11 (25th October 2018) - Linder, Markus; Glitzner, Elisabeth; Srivatsa, Sriram; Bakiri, Latifa; Matsuoka, Kazuhiko; Shahrouzi, Parastoo; Dumanic, Monika; Novoszel, Philipp; Mohr, Thomas; Langer, Oliver; Wanek, Thomas; Mitterhauser, Markus; et al.
Abstract: Osteosarcoma (OS) is a rare tumor of the bone occurring mainly in young adults accounting for 5% of all childhood cancers. Because of the limited therapeutic options, there has been no survival improvement for OS patients in the past 40 years. The epidermal growth factor receptor (EGFR) is highly expressed in OS; however, its clinical relevance is unclear. Here, we employed an autochthonous c‐Fos‐dependent OS mouse model (H2 ‐c‐fos LTR) and human OS tumor biopsies for preclinical studies aimed at identifying novel biomarkers and therapeutic benefits of anti‐EGFR therapies. We show that EGFR deletion/inhibition results in reduced tumor formation in H2‐ c‐fos LTR mice by directly inhibiting the proliferation of cancer‐initiating osteoblastic cells by a mechanism involving RSK2/CREB‐dependent c‐Fos expression. Furthermore, OS patients with co‐expression of EGFR and c‐Fos exhibit reduced overall survival. Preclinical studies using human OS xenografts revealed that only tumors expressing both EGFR and c‐Fos responded to anti‐EGFR therapy demonstrating that c‐Fos can be considered as a novel biomarker predicting response to anti‐EGFR treatment in OS patients. Synopsis: Epidermal growth factor receptor (EGFR) is frequently overexpressed in osteosarcomas (OSs). However, its clinical relevance is still under debate. In this study, the role of EGFR in OS development and progression is investigated in human OS biopsies and in genetic engineered mouse models (GEMMs) using PET/CT imaging. EGFR signalling in osteoblasts promotes OS development in GEMMs via RSK2/CREB‐dependent upregulation of the AP‐1 transcription factor c‐Fos. Patients suffering from EGFR and FOS double positive OSs exhibit reduced overall survival. In preclinical trials using orthotopic human xenografts, anti‐EGFR therapy is effective only in tumours expressing both EGFR and c‐Fos. Abstract : Epidermal growth factor receptor (EGFR) is frequently overexpressed in osteosarcomas (OSs). However, its clinical relevance is still under debate. In this study, the role of EGFR in OS development and progression is investigated in human OS biopsies and in genetic engineered mouse models (GEMMs) using PET/CT imaging.